Mapping the function of MicroRNAs as a critical regulator of tumor-immune cell communication in breast cancer and potential treatment strategies - Abdul Manap, Aimi Syamima; Wisham, Aini Athirah; Wong, Fei Wen; Ahmad Najmi, Huda Raihanah; Ng, Zhi Fei; Diba, Rubaiyat Siddique (Frontiers in Cell and Developmental Biology, 2024)
Among women, breast cancer ranks as the most prevalent form of cancer, and the presence of metastases significantly reduces prognosis and diminishes overall survival rates. Gaining insights into the biological mechanisms governing the conversion of cancer cells, their subsequent spread to other areas of the body, and the immune system's monitoring of tumor growth will contribute to the advancement of more efficient and targeted therapies. MicroRNAs (miRNAs) play a critical role in the interaction between tumor cells and immune cells, facilitating tumor cells' evasion of the immune system and promoting cancer progression. Additionally, miRNAs also influence metastasis formation, including the establishment of metastatic sites and the transformation of tumor cells into migratory phenotypes. Specifically, dysregulated expression of these genes has been associated with abnormal expression of oncogenes and tumor suppressor genes, thereby facilitating tumor development. This study aims to provide a concise overview of the significance and function of miRNAs in breast cancer, focusing on their involvement as tumor suppressors in the antitumor immune response and as oncogenes in metastasis formation. Furthermore, miRNAs hold tremendous potential as targets for gene therapy due to their ability to modulate specific pathways that can either promote or suppress carcinogenesis. This perspective highlights the latest strategies developed for miRNA-based therapies.